Birnbaum's Walt Disney World : the official vacation guide 2025 : expert advice from the inside source - Lefkon, Wendy; Safro, Jill (Editor at Disney Editions); Ward, Jessica; Hess, Jennie; Birnbaum, Alexandra Mayes; Birnbaum, Stephen (Birnbaum guides., 2024)
Presents a guide to the different sections of Walt Disney World in Orlando, Florida, including the Magic Kingdom, EPCOT, Hollywood Studios, Animal Kingdom, and the Walt Disney World resorts.